A Precaution on Using 316L Stainless Wire in Hgms Matrices. (1986) - Graham, Marshall D.
Abstract : Use of unannealed 316L stainless wire as HGMS matrix material in an application requiring frequent reversals of the magnetizing field has been noted to result in slow degradation of matrix magnetization characteristics, with attendant reductions in magnetic filtration efficiency. This alloy should be restricted to applications where field reversals are seldom required, particularly if it is exposed to corroding fluids. A similar precaution probably applies to other austenitic alloys.